The impact of COVID-19 on the changes in health behaviours among Black, Asian and Minority Ethnic (BAME) communities in the United Kingdom (UK): a scoping review - Ifunanya Nduka; Isabella Kabasinguzi; Nasreen Ali; Peter Ochepo; David Abdy; Erica Jane Cook; Chimeme Egbutah; Sally Cartwright; Gurch Randhawa (BMC, 2023)
Abstract Background The COVID-19 pandemic has led to changes in health behaviours, which include eating patterns and nutrition, smoking, alcohol consumption, sleeping patterns, physical activity and sedentary behaviour. There is a dearth of evidence reporting the impact of COVID-19 on the health behaviour of Black, Asian and minority ethnic (BAME) communities. This scoping review synthesises the available evidence on the impact of COVID-19 on the changes in health behaviours among BAME communities in the UK. Methods Following a keyword strategy, 16 electronic databases were searched for articles that met the screening criteria. These articles were then reviewed in full text. Empirical studies that assessed COVID-19 related health behaviour changes among BAME communities in the UK, conducted during the COVID-19 pandemic between July 2020 and August 2021 and published in English language, were set as inclusion criteria. An initial 2160 studies were identified in the selected databases. After removing duplications and screening the title and abstracts of the 2154 studies, only 4 studies were selected to be reviewed as they met the inclusion criteria. The included studies employed different sample sizes which ranged from N = 47 to N = 30,375 and reported several health behaviour changes. Out of the 4 included studies, 3 studies included BAME groups within their sample as a subgroup while one study focused specifically on BAME groups. Results The scoping review found that there were lower levels of physical activity among BAME groups compared to the White ethnic groups. About 41.7% of BAME groups reported drinking less alcohol than usual compared to their white counterparts who were, 34% of whom reported drinking less alcohol. Study participants from BAME backgrounds had the greatest effect of COVID-19 on decisions to purchase healthier food compared to people from white backgrounds whose decisions on purchasing healthier food were least affected. Similar to other ethnic groups the COVID-19 pandemic increased positive hygiene among BAME groups which is important in preventing other diseases and infections. . Conclusion COVID-19 had a significant impact on the health behaviours of BAME groups especially during the lockdowns as they reported changes to behaviour such as low levels of physical activities. Hence, it is important to promote health awareness among BAME groups to encourage healthy living. In addition, programmes such as physical fitness activities that favour BAME groups should be put in place, for example BAME women's walking groups to encourage people from BAME backgrounds to engage more in physical activities. Furthermore, healthy food programmes such as food parcels can be given to people from BAME backgrounds who are not able to afford healthy food due to the impact of COVID-19. Similar to other ethnic groups, the COVID-19 pandemic has increased positive hygiene among BAME groups which is important in preventing other diseases and infections.